Some Ecological Observations on the Vegetation of Mount Abu in Western Rajasthan - Gupta, Raj. K.; Saxena, S. K. (Indian Forester, 1968)
The vegetation of Mount Abu supports dry deciduous, semi-deciduous and evergreen species, which changes with the increase in altitude. Many of the plants forming the deciduous and semi-deciduous forests are common with the sub-tropical Himalayan species in the north and the semi-deciduous forests of Deccan. The ever-green species represent a humid facies of the semi-deciduous formation and do not show any resemblance with the forests classed as Bombay sub-tropical evergreen forests, earlier by Champion.